STUDY OF MAXIMUM PRECIPITATION INTENSITY TO URBAN DRAINAGE CAPABILITY (Case Study of Jl.Ir.H. Juanda Bandung City) - ARTIKA (NIM 12803016), YUDHA
Problems of water pond which occured over the urban indicate that the water volume which come into drainage exceed the normal capacities from drainage and there are other factors causing to decrease the capacities of drainage. One of matter causing increase charge the surface current is precipitation intensity. Maximum precipitation intensity increase giving major effect to level of water run off discharge at urban drainage. Calculation of discharge with the rational method use 3 primary factors, they are maximum rainfall intensity, wide of area, and run off coefficient. Maximum intensity from daily precipitation data of year 1950-2005 calculated by using Mononobe method, while data of wide area got with the direct measurement in field. Calculation of water run off discharge from yearly period 1950-2005 maximum precipitation intensity at Jl.Ir.H. Juanda by using rational method indicates that the water run off discharge is larger than maximum discharge of existing drainage dimension which equal to 0.52 m3/s. From that research result the existing drainage dimension need to be considered, especially for future.